Applying Baydur Composite Material in Designing Automotive Door Beams. (September 2020) - Ma, Lingyue; Liu, Mingji; Chen, Zhiyuan
Abstract: This work studied the application of Baydur pultrusion composite material to the side door anti-collision beams of cars. The beams are currently made of high-strength steel materials and arranged inside the door to meet the requirements of road safety laws and regulations. The Baydur pultrusion composite material has many advantages that metal steel does not have. Based on the characteristics of the composite materials and safety standards for vehicle side collisions, we proposed a design to use Daybur composite material instead of steel as the anti-collision beam material in automobile side doors. The structural design of the beam with the composite material is optimized so that it can effectively improve the safety performance during side collisions and reduce the body weight to save fuel consumption. The feasibility of the design has been investigated from three aspects of technical manufacturing, safety performance and market application. The application of the composite material in the anti-collision beams will provide new options for the safety and energy efficiency of civil vehicles.